-4-7x+3x=-16

Simple and best practice solution for -4-7x+3x=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-7x+3x=-16 equation:


Simplifying
-4 + -7x + 3x = -16

Combine like terms: -7x + 3x = -4x
-4 + -4x = -16

Solving
-4 + -4x = -16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -4x = -16 + 4

Combine like terms: -4 + 4 = 0
0 + -4x = -16 + 4
-4x = -16 + 4

Combine like terms: -16 + 4 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 6x-y=-7 | | 2n-4n=14 | | X+3*2=15 | | 6x-7x=7 | | -3(x+5)+2=4(x+6) | | 3(x+5)+2=4(x+6) | | x-x=0 | | (3x-2)(6x+1)=0 | | -8n+3n=0 | | 4y+7x+8=0 | | 2(x-3)-4(x+6)=4x-6 | | 5-6x-8x=-9 | | 17-6x=-9x+11 | | -3x+3x=3 | | n+3n=24 | | -2x(2x-3)=12 | | 3d^3-48d=0 | | 2x+5y=0 | | 2x+5y=17 | | -3*(5-5x)=7*(-8x-2)-427 | | 3.2-0.6x=0.4(x-2) | | -x-3x=-24 | | 4x-x=6 | | -12=12(h-5) | | -6x-4x= | | 5y^2-25=0 | | 7*(7-x)=50-2*(3+4x) | | 4x+3y=17 | | 1+4n-7=-2 | | (2+3x)*3-128+12x=x+6*(2x+1) | | 4-3y=21 | | (2x+1)(2X-3)=(x+2)(4x-5) |

Equations solver categories